Temperature Effects on Physiochemical Characteristics of Sugar-Based Natural Deep Eutectic Solvents - Mohammad Tarikuzzaman; Viral Sagar; Mark James Wong; Joan G. Lynam (Advances in Materials Science and Engineering)
Phase behavior, density, viscosity, conductivity, pH, and surface tension were measured, and FTIR was performed for a series of mixtures of sugar (glucose, fructose, xylose, and sucrose), water, and choline chloride (ChCl) at specific molar ratios. These mixtures, called sugar-based natural deep eutectic solvents (NADESs), were investigated as a function of temperature. Contact angle measurements indicated that NADES exhibited slightly lower wettability but higher surface tension than water. Temperature was found to greatly impact density, viscosity, and conductivity. The optimum water molar ratio for lower viscosity was found at ratios higher than those reported in the literature, indicating that the NADES investigated may have industrial process applications.